If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-11=4x-4
We move all terms to the left:
x-11-(4x-4)=0
We get rid of parentheses
x-4x+4-11=0
We add all the numbers together, and all the variables
-3x-7=0
We move all terms containing x to the left, all other terms to the right
-3x=7
x=7/-3
x=-2+1/3
| 2x+1/4=9/4 | | −16−7x=138+7x. | | 6x+5+4=6x+9 | | 3/x=8/12 | | 52-5b=17 | | 1.4+x=8 | | 4•x+6=6•x-4 | | 98x-42=65x+45 | | 6x-54=7x-56 | | 6a/5-2a/3=4/3 | | -3c=-15/(-3) | | 11(9x-55)=88 | | -3c=-15 | | 2)x+1.25)=3.5 | | 0,3 x+0,5=1,1 | | -1.5+8=2-3x | | -4x2=-144 | | 3/16x=0 | | 3/5=x/90 | | (5x+3)(4x+9)+(5x+3)(-7x-4)=0 | | 81x2+144x+64=0 | | -3c=-30+15 | | (-9m-6)(5m-6)(8m-8)=0 | | (-5r+8)(7r+7)=0 | | 5/4x-1/2=5/6 | | (-3d+8)(3d-10)=0 | | 254-150-y=27+61 | | -5x2=-20 | | (8x-7)(-9x+9)-(8x-7)(6x+7)=0 | | 8x-3=2x-39 | | −3−(x−4)+2(x+3)=6−(x+1) | | (-2r-1)(-2r-6)(2r+6)=0 |